Pencegahan Sindrom Delirium Akut pada Pasien Lansia di Rawat Inap - Vera, Vera (UI Scholars Hub, 2025)
Acute delirium syndrome is often found in hospitalized older patients, requiring longer hospital stay and higher hospital cost. Studies showed that 40% of these delirium cases in older patients may be prevented with multicomponent intervention based on National Institute for Health and Clinical Excellence (NICE) and Hospital Elder Life Program (HELP) guidelines. This article explained multicomponent intervention, which includes protocols for disorientation, dehydration, hypoxia, constipation, malnutrition, pain control, infection control, infection prevention, drugs evaluation, early mobilization, and education for patients’ family / caregiver. Prevention of acute delirium syndrome in hospitalized older patients will reduce the medical cost and distress among patients’ family.